ASSESSING LAND USE AND LAND COVER CHANGE IMPACT ON FLASH FLOODS IN KASARANI CONSTITUENCY, KENYA - Ominde, Japheth (IJRDO - Journal of Social Science and Humanities Research, 2022)
Kasarani Constituency in Nairobi County, Kenya is one of the areas that experienced frequent flash floods over the last decade. Anthropogenic activities such as the construction of roads, buildings, and industrialization are identified as key drivers of change in LULC. The aim of this study was to assess the impact of LULC change on flooding in the Kasarani constituency by comparing Spectral indices from Landsat images captured before, during, and after floods between 2013 and 2020. The value of NDVI and MSAVI indices declined during flood days indicating that the vegetation was covered with water while the NDMI value increased during flood days indicating a water-logged surface. The Digital Elevation Model of the study area was created to identify the low-lying areas and river channels that were identified as high flood risk areas. In order to reduce vulnerability to frequent floods, there is a need to identify safe areas for evacuation as well as raised areas for settlement.